Control systems in design and technology [videorecording] (Films Media Group, 2012)
As technology becomes progressively more complex and an intrinsic part of modern work and life, we are increasingly reliant on computer-controlled technology to extend human capabilities. This program introduces computer-controlled systems, block diagrams, open and closed loop systems, microprocessors, and sensors and actuators. In addition, the video examines EFTPOS machines, robots, manufacturing and product control, and multimedia entertainment, educational, and medical applications.